Community-Based Family Workshop Intervention Improved the Social Adaptation of Left-Behind Children in Rural China - Zhang, Xiu; Li, Mengjie; Guo, Li; Zhu, Yanna (Frontiers in Public Health, 2020)
Purpose: With the rapidly developing economy in China, there are more than 50 million left-behind children (LBC) in rural China, whose social adaptation has become a public concern. Thus, the current study aimed to investigate the effect of community-based family workshop intervention on social adaptation among rural LBC in China. Methods: A cluster randomized trial was conducted with 104 LBC, in which 66 LBC-caregivers dyads received guidance from community-based family workshop for 6 months, while the controls (LBC n = 38) received routinely parenting guidance. Social adaptation of the children was assessed by the Strength and Difficulties Questionnaire (SDQ) at the beginning and the end of the intervention. Findings: Compared with controls, results showed remarkable improvement on emotional symptoms (P = 0.050), peer problems (P = 0.050), and total difficulties score (TDS, P = 0.040) in the intervention group, especially those aged 3–6 years. Moreover, SDQ score of TDS (P = 0.039), peer problems (P = 0.013), and hyperactivity–inattention (P = 0.023) decreased after intervention in boys aged 3–6 years, while emotional symptoms (P = 0.048) in girls. Finally, improvement on peer problems (P = 0.005) was observed in participants with high TDS. Conclusions: The findings suggest that community-based family workshop intervention can improve social adaptation of rural LBC. Moreover, this effect was different in boys and girls and also affected by age and baseline total difficulties. The results indicated that community-based family workshop intervention can be implemented in rural China to improve mental and behavioral health among LBC in the future.